Entrepreneurship Education, Self-Confidence, and Students’ Career Choice as an Entrepreneur - Abdullah Al- Mamun; Shaw Pui Fong; Noorshella Che Nawi; Siti Farhah Fazira Shamsudin (2015)
Introduction-Entrepreneurship is perceived as an accurate field and should be given priority to produce graduates who are mentally strong and competitive. Malaysian government and the higher education sector have been working together over a number of years to increase the impact of the higher education on business and society. The Ministry of Education has instructed all local public universities to pursue the entrepreneurship curriculum, content and programs as a preparation for students to venture into business (Othman, Othman, and Ismail 2012)